Low-carbohydrate ketogenic diets in male endurance athletes demonstrate different micronutrient contents and changes in corpuscular haemoglobin over 12 weeks - McSwiney, M. T.; Doyle, L. (Sports, 2019)
High-carbohydrate (HC) diets and low-carbohydrate ketogenic diets (LCKD) are consumed by athletes for body composition and performance benefits. Little research has examined nutrient density of self-selected HC or LCKDs and consequent effect on blood haematology in an athlete population. Using a non-randomised control intervention trial, nutrient density over 3 days, total blood count and serum ferritin, within endurance athletes following a self-selected HC (n = 11) or LCKD (n = 9) over 12 weeks, was examined. At week 12, HC diet participants had greater intakes of carbohydrate, fibre, sugar, sodium, chloride, magnesium, iron, copper, manganese and thiamine, with higher glycaemic load (GL), compared to LCKD participants (P < 0.05). LCKD participants had greater intakes of saturated fat, protein, a higher omega 3:6 ratio, selenium, vitamins A, D, E, K1, B12, B2, pantothenic acid and biotin. Mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) decreased in LCKD participants after 12 weeks but remained unchanged in HC participants, with no change in serum ferritin in either group. This analysis cannot examine nutrient deficiency, but athletes should be made aware of the importance of changes in dietary type on micronutrient intakes and blood haematology, especially where performance is to be considered.